Canva Training to Increase Digitalization of Micro, Small and Medium Enterprises (MSMEs) in Kenteng Village - Muhammad, Faizin; Intan Damai Wati; Najmia Iffatunnisa; Muhammad Ali Abdul Aziz; Annisa Maya Khoerunnisa; Muhammad Dain Jaddun Uzzais; Novita Rika Ulfana; Fita Nurotul Faizah (Khidmatuna (Jurnal Pengabdian Kepada Masyarakat), 2024)
This community engagement initiative addresses the critical challenge of limited digital literacy and skills among Micro, Small, and Medium Enterprises (MSMEs) in Kenteng Village by implementing a targeted training program on the utilization of Canva as a modern promotional tool. Employing a mixed-methods approach, the study combines observational techniques, needs assessment, and participatory training sessions that integrate theoretical frameworks on digital transformation with hands-on practice in Canva. The results demonstrate a statistically significant improvement in participants' knowledge and practical skills, enabling them to independently design promotional materials such as catalogs, posters, and social media content. The intervention serves as a strategic catalyst for enhancing product visibility, competitive advantage, and digital adaptability among Kenteng Village MSMEs. These findings underscore the importance of context-specific digital literacy programs in fostering sustainable economic growth in rural communities.